Revelation 1-3 in Christian Arabic commentary: John's first vision and the letters to the seven churches - Davis, Stephen J. (Christian Arabic texts in translation, 2019)
Introduction: two Arabic commentaries on the Apocalypse of John in historical and cultural context / Stephen J. Davis -- Bulus al-Bushi on Revelation 1-3: Christology and Christian-Muslim encounter / Shawqi Talia and Stephen J. Davis -- Ibn Katib Qaysar on visions, angels, prophets, and dreams / Stephen J. Davis -- Ibn Katib Qaysar on Revelation 1-3: the first vision and the letters to the seven churches / T. C. Schmidt, with contributions by Stephen J. Davis -- Bulus al-Bushi, Commentary on the Apocalypse of John, ch. 1-3 / translated by Shawqi Talia; edited by Stephen J. Davis -- Ibn Katib Qaysar, Commentary on the Apocalypse of John, ch. 1-3 / translated by Stephen J. Davis and T. C. Schmidt